Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Nguyễn Trà My
Phần a)
\(3\times\left(\frac{1}{2}-x\right)+\frac{1}{3}=\frac{7}{6}-x\)
\(32-3x+13=76-x\)
\(116-3x=76-x\)
\(116-76=3x-x\)
\(46=2x\)
\(x=46\div2\)
\(x=13\)
Bài 1:
- \(\dfrac{11}{2}x\) + 1 = \(\dfrac{1}{3}x-\dfrac{1}{4}\)
- \(\dfrac{11}{2}\)\(x\) - \(\dfrac{1}{3}\)\(x\) = - \(\dfrac{1}{4}\) - 1
-(\(\dfrac{33}{6}\) + \(\dfrac{2}{6}\))\(x\) = - \(\dfrac{5}{4}\)
- \(\dfrac{35}{6}\)\(x\) = - \(\dfrac{5}{4}\)
\(x=-\dfrac{5}{4}\) : (- \(\dfrac{35}{6}\))
\(x\) = \(\dfrac{3}{14}\)
Vậy \(x=\dfrac{3}{14}\)
Bài 2: 2\(x\) - \(\dfrac{2}{3}\) - 7\(x\) = \(\dfrac{3}{2}\) - 1
2\(x\) - 7\(x\) = \(\dfrac{3}{2}\) - 1 + \(\dfrac{2}{3}\)
- 5\(x\) = \(\dfrac{9}{6}\) - \(\dfrac{6}{6}\) + \(\dfrac{4}{6}\)
- 5\(x\) = \(\dfrac{7}{6}\)
\(x\) = \(\dfrac{7}{6}\) : (- 5)
\(x\) = - \(\dfrac{7}{30}\)
Vậy \(x=-\dfrac{7}{30}\)
\(2\left(\frac{3}{2}-x\right)-\frac{1}{3}=7x-\frac{1}{4}\)
\(\Leftrightarrow3-2x-\frac{1}{3}=7x-\frac{1}{4}\)
\(\Leftrightarrow-2x+\frac{8}{3}=7x-\frac{1}{4}\)
\(\Leftrightarrow\frac{1}{4}+\frac{8}{3}=7x+2x\)
<=> 9x = 35/12
=> x = 35/12 . 1/9 = 35/108
a; \(x\) - \(\dfrac{3}{5}\) = 1 - \(\dfrac{4}{5}\) + \(\dfrac{1}{6}\)
\(x\) - \(\dfrac{3}{5}\) = \(\dfrac{30}{30}\) - \(\dfrac{24}{30}\) + \(\dfrac{5}{30}\)
\(x\) - \(\dfrac{3}{5}\) = \(\dfrac{6}{30}\) + \(\dfrac{5}{30}\)
\(x\) - \(\dfrac{3}{5}\) = \(\dfrac{11}{30}\)
\(x\) = \(\dfrac{11}{30}\) + \(\dfrac{3}{5}\)
\(x\) = \(\dfrac{11}{30}\) + \(\dfrac{18}{30}\)
\(x\) = \(\dfrac{29}{30}\)
Vậy \(x\) = \(\dfrac{29}{30}\)
b; (- \(\dfrac{10}{4}\)) + \(\dfrac{1}{4}\) = \(\dfrac{3}{4}\) thế \(x\) của em đâu nhỉ???
c; - \(\dfrac{3}{2}\) + (\(x\) - \(\dfrac{1}{2}\)) = \(\dfrac{1}{2}\)
\(x\) - \(\dfrac{1}{2}\) = \(\dfrac{1}{2}\) + \(\dfrac{3}{2}\)
\(x\) - \(\dfrac{1}{2}\) = 2
\(x\) = 2 + \(\dfrac{1}{2}\)
\(x\) = \(\dfrac{4}{2}\) + \(\dfrac{1}{2}\)
\(x\) = \(\dfrac{5}{2}\)
Vậy \(x=\dfrac{5}{2}\)
\(2x+\frac{1}{2}=\frac{-5}{3}\)
\(2x=\frac{-5}{3}-\frac{1}{2}\)
\(2x=\frac{-10}{6}-\frac{3}{6}\)
\(2x=\frac{-13}{6}\)
\(x=\frac{-13}{6}:2\)
\(x=\frac{-13}{12}\)
3) \(\frac{x-3}{x-2}=\frac{4}{7}\)
\(\Rightarrow\left(x-3\right).7=\left(x-2\right).4\)
\(\Rightarrow7x-21=4x-8\)
\(\Rightarrow7x-4x=\left(-8\right)+21\)
\(\Rightarrow3x=13\)
\(\Rightarrow x=13:3\)
\(\Rightarrow x=\frac{13}{3}\)
Vậy \(x=\frac{13}{3}.\)
4) \(\left|x\right|+3,5=0\)
\(\Rightarrow\left|x\right|=0-3,5\)
\(\Rightarrow\left|x\right|=-3,5\)
Vì \(\left|x\right|\ge0\) \(\forall x.\)
\(\Rightarrow\left|x\right|>-3,5\)
\(\Rightarrow\left|x\right|\ne-3,5\)
Vậy \(x\in\varnothing.\)
5) \(\left|x+\frac{1}{3}\right|-4=1\)
\(\Rightarrow\left|x+\frac{1}{3}\right|=1+4\)
\(\Rightarrow\left|x+\frac{1}{3}\right|=5.\)
\(\Rightarrow\left[{}\begin{matrix}x+\frac{1}{3}=5\\x+\frac{1}{3}=-5\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5-\frac{1}{3}\\x=\left(-5\right)-\frac{1}{3}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\frac{14}{3}\\x=-\frac{16}{3}\end{matrix}\right.\)
Vậy \(x\in\left\{\frac{14}{3};-\frac{16}{3}\right\}.\)
Chúc bạn học tốt!
\(a,x.\frac{-3}{7}=\frac{4}{21}\)
\(x=\frac{4}{21}:\frac{-3}{7}\)
\(x=\frac{-4}{9}\)
\(b,\frac{-4}{7}:x=\frac{2}{5}\)
\(x=\frac{-4}{7}:\frac{2}{5}\)
\(x=\frac{-10}{7}\)
\(c,x+\frac{1}{12}=\frac{-3}{8}\)
\(x=\frac{-3}{8}-\frac{1}{12}\)
\(x=\frac{-11}{24}\)
\(d,\frac{2}{15}-x=\frac{-3}{10}\)
\(x=\frac{2}{15}+\frac{3}{10}\)
\(x=\frac{13}{30}\)
\(e,-x+\frac{4}{5}=\frac{1}{2}\)
\(-x=\frac{-3}{10}\)
\(x=\frac{3}{10}\)
\(f,\frac{3}{4}.\left(x+1\right)-\frac{1}{2}=\frac{3}{7}\)
\(\frac{3}{4}.\left(x+1\right)=\frac{13}{14}\)
\(x+1=\frac{26}{21}\)
\(x=\frac{5}{21}\)
\(\frac{-3}{2}-2x+\frac{3}{4}=-2\)
\(\frac{-3}{2}-2x=\frac{-11}{4}\)
\(2x=\frac{-3}{2}+\frac{11}{4}\)
\(2x=\frac{-17}{4}\)
\(x=\frac{-17}{8}\)
\(h,-x+\frac{4}{5}=\frac{1}{2}\)
\(-x=\frac{-3}{10}\)
\(x=\frac{3}{10}\)
chúc bạn học tốt !!!